Nosy confirmation: reconstitution of the characteristic odor of softwood via quantitative analysis and human sensory evaluation - Schreiner, Linda; Ortner, Eva; Büttner, Andrea (Analytical and Bioanalytical Chemistry, 2020)
The significance of wood odors beyond flavoring effects for barbecues and wine aged in barrels has recently been under discussion. Wood has an immense influence on our physical and mental condition through our palate, such as positive health and mood-stimulating effects. As a result of increased public interest, the key odorants from various natural wood species were recently decoded. To gain profound insights into the contribution of single odorants to the overall scent of distinct wood types, this study compares several softwood species (Scots pine, incense cedar, European larch, Norway spruce, and white fir) by odor profile analysis. Nine odor-active constituents, which were previously detected in those woods, were quantified using stable isotope dilution analysis (SIDA). Odor activity values (OAVs) calculated on the basis of odor thresholds (OTs) determined in cellulose revealed hexanal, octanal, (E)-non-2-enal, p-cresol, vanillin, and thymoquinone as dominant odorants for wood odor. Recombination experiments by mixing the odorants in their naturally occurring concentrations in a cellulose matrix confirmed the successful characterization of the key odorants for Scots pine and incense cedar wood.
CRIS-Team Scopus Importer:2020-02-18
Keywords: Odor activity values; Odor recombination; Thymoquinone; Wood; α-Pinene